2002
DOI: 10.1159/000063806
|View full text |Cite
|
Sign up to set email alerts
|

Vinblastine and Interferon-Gamma Combination with and without 13-Cis Retinoic Acid for Patients with Advanced Renal Cell Carcinoma

Abstract: Background: The aim of this study is firstly to determine the response rates and toxicity of two regimens containing vinblastine (VBL) in combination with interferon-gamma (IFN-γ) in the treatment of patients with advanced renal cell carcinoma (RCC), and secondly to evaluate the additional efficacy of 13-cis retinoic acid (13-CRA) in RCC. Methods: Twenty-nine patients were included in the first trial (Trial 1) and 40 in the second one (Trial 2). The therapy given in Trial 1 consisted of VBL 0.15 mg/kg i.v. eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Recently, however, Vaishampayan et al [49] reported that this combination had only minimal activity in advanced renal cell carcinoma. Further, the addition of 13-cis-RA to vinblastine and interferon gamma did not appear to increase the efficacy of this combination in renal cell carcinoma, a highly chemoresistant tumor [50]. Clearly, 13-cis-RA has potential for the treatment of advanced cancers.…”
Section: Role Of Retinoids In the Treatment Of Cancermentioning
confidence: 95%
“…Recently, however, Vaishampayan et al [49] reported that this combination had only minimal activity in advanced renal cell carcinoma. Further, the addition of 13-cis-RA to vinblastine and interferon gamma did not appear to increase the efficacy of this combination in renal cell carcinoma, a highly chemoresistant tumor [50]. Clearly, 13-cis-RA has potential for the treatment of advanced cancers.…”
Section: Role Of Retinoids In the Treatment Of Cancermentioning
confidence: 95%
“…Conventional cytotoxic chemotherapy and radiotherapy are largely ineffective (3), response rates to interferon (IFN)-• and IFN-ß treatments range from 10 to 20% (4), and long-lasting responses to interleukin (IL)-2-based therapy are obtained in only 4-5% of the treated patients (5). Although there have been numerous attempts to increase these low response rates by using combination therapies, such as vinblastine and IFNs, the reported effects have not been dramatic (6,7). Further improvement awaits the development of a more effective systemic therapy.…”
Section: Introductionmentioning
confidence: 99%